Interdisciplinary structury analysis systems in the field of artificial intelligence technologies - A. I. Loiko (Системный анализ и прикладная информатика)
The article discusses the methodological strategies of integrated computer logistics in the field of artificial intelligence, focused on the tasks of the cognitive economy. The mechanism of the methodological synthesis of disciplinary structures into the system of cognitive sciences and the advantages research programs arising from this mechanism are shown.